2015
DOI: 10.3329/jbs.v21i0.22516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the abundance and species composition of Phytoplankton of Moiur river, Khulna

Abstract: Context: Phytoplanktonic community structure in an aquatic body embodies the energy transfer through this phase and indicates the tropic status. Objectives: The present study was conducted to assess the phytoplankton abundance and species composition of Mouri River, Khulna, Bangladesh. Materials and Methods: Water samples were collected from six different stations once in a week for a period of 6 months (February- July) 2010. Results: In total 48 different species of 23 genus and 4 families were identified. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…It was observed that TDS was negatively correlated with total phytoplankton, all algal groups and species diversity. This nding was agreed with previous studies that showed the same negative correlation between phytoplankton population and TDS concentration (Rahi et al 2013;Elshobary et al 2020), illustrating the negative effect of inorganic remains materials of TDS on the phytoplankton growth. While Phytoplankton density positively correlated with nutrient content such as Nitrate and silicate.…”
Section: Phytoplankton Abundance In Relation To Some Physico-chemicalsupporting
confidence: 93%
“…It was observed that TDS was negatively correlated with total phytoplankton, all algal groups and species diversity. This nding was agreed with previous studies that showed the same negative correlation between phytoplankton population and TDS concentration (Rahi et al 2013;Elshobary et al 2020), illustrating the negative effect of inorganic remains materials of TDS on the phytoplankton growth. While Phytoplankton density positively correlated with nutrient content such as Nitrate and silicate.…”
Section: Phytoplankton Abundance In Relation To Some Physico-chemicalsupporting
confidence: 93%
“…The Indian major carp Rohu ( Labeo rohita ) is an important freshwater aquaculture species and a major species in inland open water systems across the entire Indian Subcontinent, including Bangladesh (Rahi et al., 2013; Shah et al., 2011; Sabbir et al., 2017). This single species contributes ≈8% of the total freshwater fish production in Bangladesh (Ali et al., 2015; Department of Fisheries [DOF], 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on physicochemical parameters and phytoplankton community of other rivers are conducted, including the Meghna River (Ahmed 2003, Ahsan et al 2012; Moiur river (Rahi et al 2015); Dhaleshwari river (Islam et al 2012); Karnafully river (Sarwar et al 2010); Jamuna River (Uddin et al, 2014). Some brief studies on physicochemical parameters and phytoplankton community of the Halda River (Parta andAzadi 1987, Parvez et al 2019;Nahid et al 2020) were done, but no descriptive and vertical abundance of phytoplankton was performed.…”
Section: Introductionsmentioning
confidence: 99%